MADS-box encoding gene Tunicate1 positively controls maize yield by increasing leaf number above the ear - Yan Li; Jian Wang; Shuyang Zhong; Qiang Huo; Qun Wang; Yunlu Shi; Hangqin Liu; Jiacheng Liu; Yang Song; Xiaojian Fang; Zhongwei Lin (Nature Communications)
Abstract The leaves above the ear serve as a major source of carbohydrates for grain filling in maize. However, increasing the number of leaves above the ear to strengthen the source and improve maize yield remains challenging in modern maize breeding. Here, we clone the causative gene of the quantitative trait locus (QTL) associated with the number of leaves above the ear. The causative gene is the previously reported MADS-box domain-encoding gene Tunicate1 (Tu1), which is responsible for the phenotype of pod corn or Tunicate maize. We show that Tu1 can substantially increase the leaf number above the ear while maintaining the source‒sink balance. A distal upstream 5-base pair (bp) insertion of Tu1 originating from a popcorn landrace enhances its transcription, coregulates its plastochron activators and repressors, and increases the number of leaves above the ear. Field tests demonstrate that the 5-bp insertion of Tu1 can increase grain yields by 11.4% and 9.5% under regular and dense planting conditions, respectively. The discovery of this favorable Tu1 allele from landraces suggests that landraces represent a valuable resource for high-yield breeding of maize.